Taiwan’s enterprise value vs. carbon emission - Yu-Tai Yang; Hong-Yu Lin; Tzu-Ling Tseng (All Earth)
Under the impact of climate change, both the environment and the economy are changing rapidly, and companies must respond to this crisis when forming their business strategies. This study investigates whether the impact of company performance differs depending on the amount of its carbon emissions via research period is from 2014 to 2020 from Taiwan Economic Journal. Earnings per share and debt ratio are used as the independent variables, gross margin as enterprise value is used as the dependent variable, and carbon emission intensity ratio is used as the conversion variable. Empirical analysis was conducted using a panel smooth transition regression model. Results show that the relationship between the carbon emissions of a company and its enterprise value is nonlinear, and that at less than a specific threshold value for carbon emissions, the financial performance and enterprise value of a corporate are positively correlated.